Non-anaesthetist-administered ketamine for emergency caesarean section in Kenya: cost-effectiveness analysis. Issue 10 (5th October 2022) - Resch, Stephen Charles; Suarez, Sebastian; Omotayo, Moshood Olanrewaju; Griffin, Jennifer; Sessler, Daniel; Burke, Thomas
Abstract : Objectives: Lack of anaesthesia services is a frequent barrier to emergency surgeries such as caesarean delivery in Kenya. This study aimed to estimate the survival gains and cost-effectiveness of scaling up the Every Second Matters (ESM)-Ketamine programme that trains non-anaesthetist providers to administer and monitor ketamine during emergency caesarean deliveries. Setting: Hospitals in Kenyan counties with low rates of caesarean delivery. Participants: Patients needing emergency caesarean delivery in settings without availability of standard anaesthesia service. Interventions: Simulated scales up of the ESM-Ketamine programme over 5 years (2020–24) was compared with status quo. Outcome measures: Cost of implementing the programme and corresponding additional emergency caesarean deliveries. Maternal and fetal/neonatal deaths prevented, and corresponding life-years gained due to increased provision of emergency caesarean procedures. Cost-effectiveness was assessed by comparing the cost per life-year gained of the ESM-Ketamine programme compared with status quo. Results: Over 5 years, the expected gap in emergency caesarean deliveries was 157 000. A US1.2 million ESM-Ketamine programme reduced this gap by 28 700, averting by 316 maternal and 4736 fetal deaths and generating 331 000 total life-years gained. Cost-effectiveness of scaling up the ESM-Ketamine programme was US44 per life-year gained in the base case and US251 in the most pessimistic scenario—a very good value for Kenya at less than 20% of per capita GDP per life-year gained. Conclusion: In areas of Kenya with significant underprovision of emergency caesarean delivery due to a lack of availability of traditional anaesthesia, an ESM-Ketamine programme is likely to enable a substantial number of life-saving surgeries at reasonable cost.